2015
DOI: 10.1017/edp.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Australian Racism, Acceptance, and Cultural-Ethnocentrism Scale (RACES)

Abstract: Existing Australian measures of racist attitudes focus on single groups or have not been validated across the lifespan. To redress this, the present research aimed to develop and validate a measure of racial, ethnic, cultural and religious acceptance — the Australian Racism, Acceptance, and Cultural-Ethnocentrism Scale (RACES) — for use with children, adolescents and adults. Interviews and focus groups were conducted with 30 adolescents in Victoria, Australia, to develop the instrument, which was pilot tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…From December 2011 to March 2012, a qualitative study was conducted among young Australians on their conceptualisations of and experiences with racism, to generate sufficient data to form the basis of a scale (detailed elsewhere; [ 31 ]). This study demonstrated a consistent explanatory model for understanding racism across groups [ 36 ]. The qualitative data, which provided insight into Australian lay understandings of racism [ 31 ], were supplemented and complemented by an extensive and comprehensive literature review on the conceptual racism literature and existing instruments, to create the preliminary measure.…”
Section: Measuring Racismmentioning
confidence: 67%
See 4 more Smart Citations
“…From December 2011 to March 2012, a qualitative study was conducted among young Australians on their conceptualisations of and experiences with racism, to generate sufficient data to form the basis of a scale (detailed elsewhere; [ 31 ]). This study demonstrated a consistent explanatory model for understanding racism across groups [ 36 ]. The qualitative data, which provided insight into Australian lay understandings of racism [ 31 ], were supplemented and complemented by an extensive and comprehensive literature review on the conceptual racism literature and existing instruments, to create the preliminary measure.…”
Section: Measuring Racismmentioning
confidence: 67%
“…In addition, 402 community individuals aged 15 years or older also participated. Adolescents and adults from six of the seven Australian states and territories participated in the research (for details see: [ 36 ]). It was considered important to examine the children, adolescents, and adults separately due to differences in their general developmental stage [ 40 42 ] and the level of crystallisation of their racial attitudes [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations